Operation characteristics and carbon corrosion of PEMFC (Proton exchange membrane fuel cell) with dead-ended anode for high hydrogen utilization. (November 2015) - Chen, Ben; Ke, Wandi; Luo, Maji; Wang, Jun; Tu, Zhengkai; Pan, Mu; Zhang, Haining; Liu, Xiaowei; Liu, Wei
Abstract: PEMFC (Proton exchange membrane fuel cell) operated under dead-ended anode mode is an effective and simple device for high hydrogen utilization. Herein, the operation characteristics of PEMFC with dead-ended anode are systematically investigated under various operating temperature, anode inlet pressure, and cathode stoichiometry. In each operating parameter, the solenoid valve located at the anode outlet is closed all the time and the hydrogen utilization reaches 100%. It has been found that fuel cell with dead-ended anode can operate continuously for 26 h with slight decrease in output voltage under 600 mA cm −2 at 65 °C, 80% of RH (relative humidity) with hydrogen inlet pressure of 0.4 bar gauge and oxygen stoichiometry of 4.0. After accumulated 150 h operation under dead-ended anode mode, the degradation of according MEA (membrane electrode assembly) has been analyzed using CV (cyclic voltammetry) and cross-sectional morphology. The results show that the accumulation of water induced corrosion of catalyst layer is responsible for the decrease in ECSA (electrochemical surface area) of catalyst layer and the according degradation of cell performance. Moreover, the degradation of catalyst layer became much more serious at the vicinity of cathode outlet than the other regions. Highlights: PEMFC operated for 26 h in dead-ended anode model with 100% hydrogen utilization. Water-flooding induced carbon corrosion in both anode and cathode sides. Catalyst degraded much more seriously at the cathode outlet than the other regions.